2020
DOI: 10.1111/1745-9133.12487
|View full text |Cite
|
Sign up to set email alerts
|

Evidence concerning the regulation of firearms design, sale, and carrying on fatal mass shootings in the United States

Abstract: Research Summary We used data from the FBI's Supplemental Homicide Reports and other publicly available databases to calculate state‐level annual incidence of fatal mass shootings for 1984–2017. Negative binomial regression models were used to estimate the associations between changes in key gun laws and fatal mass shootings. Handgun purchaser licensing laws and bans of large‐capacity magazines (LCMs) were associated with significant reductions in the incidence of fatal mass shootings. Other laws commonly advo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 23 publications
8
56
1
Order By: Relevance
“…Similarly, Webster, McCourt, Crifasi, and Booty, in their state‐level panel study (, this issue), suggested that the rate of mass murder incidents and victims did not change significantly during the ban years in comparison with their averages across the pre‐ban (1984–1994) and post‐ban (2005–2017) periods after controlling for state gun laws, time trends, state‐level fixed effects, and various social factors. The results of their analyses, however, also show upward post‐ban trends in the mass murder victim rate and the average number of victims killed per incident that accelerated dramatically after 2014.…”
Section: Effects Of Assault Weapon and Large‐capacity Magazine Restrimentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, Webster, McCourt, Crifasi, and Booty, in their state‐level panel study (, this issue), suggested that the rate of mass murder incidents and victims did not change significantly during the ban years in comparison with their averages across the pre‐ban (1984–1994) and post‐ban (2005–2017) periods after controlling for state gun laws, time trends, state‐level fixed effects, and various social factors. The results of their analyses, however, also show upward post‐ban trends in the mass murder victim rate and the average number of victims killed per incident that accelerated dramatically after 2014.…”
Section: Effects Of Assault Weapon and Large‐capacity Magazine Restrimentioning
confidence: 94%
“…Most notably, Webster et al. (), in their state‐level panel analysis of mass murders from 1984 through 2017, suggested that state LCM bans reduce mass murder incidents (4+ killed) and fatalities whereas AW‐specific restrictions do not. Controlling for several types of gun laws, gun availability, socioeconomic variables, time trends, and other state‐level differences, Webster et al.…”
Section: Effects Of Assault Weapon and Large‐capacity Magazine Restrimentioning
confidence: 99%
“…Approximately 22 percent of recent firearm acquisitions in the United States occur without a criminal background check (some of which occur even in states in which background checks are required for private sales; Miller, Hepburn, & Azrael, ). Research findings on this issue indicate that when states have a licensing system in place that requires all prospective firearm purchasers to obtain a permit from local officials (who conduct the background checks) prior to purchase, there is an associated lower risk of mass shootings in those states (Webster et al., ). States and the federal government may consider passing permit‐to‐purchase legislation to reduce mass shootings.…”
Section: Discussionmentioning
confidence: 99%
“…Mass shootings and other crimes committed with high‐capacity semiautomatics (including assault weapons and other models) have been rising since the expiration of the federal ban on assault weapons, and this results in greater numbers of persons killed and wounded per incident as compared to attacks with other types of firearms (Koper, , this issue; also see Lankford & Silver, ). States with magazine capacity restrictions, however, have fewer mass shootings (Webster, McCourt, Crifasi, & Booty, , this issue). To staunch further growth in the stock of high‐capacity semiautomatic weapons, we recommend the following: For new sales, limit the magazine capacity to 10 rounds.…”
Section: Staunching the Growth Of High‐capacity Firearmsmentioning
confidence: 99%
“…Prohibited gun possessors have been responsible for close to half of recent mass shootings (Zeoli & Paruk, , this issue); universal background checks would reduce the ease with which such offenders can obtain firearms. Universal background checks are most effective in reducing mass shootings and other gun violence when they are administered through firearms licensing and permit systems that require buyers to go through rigorous screening by state or local law enforcement authorities (Webster et al., ). Adopt extreme risk protection orders (ERPOs) to disarm high‐risk individuals. Mass shooters often present warning signs of their dangerousness or intentions (see below).…”
Section: Curtailing Access To Firearms For Individuals Who Are a Dangmentioning
confidence: 99%